French as a Foreign Language: The Literary Enterprise of Antoine Volodine - David Bellos (Studies in 20th & 21st Century Literature, 2012)
Volodine’s fictions all resemble each other save for names and settings. They expose a world where the Revolution has failed and its protagonists are either dead, incarcerated, or holed up in the putrefying carcass of an abandoned building. Protagonists keep the memory of their political dreams alive by telling the stories of lost comrades, in works tapped out in code on the drainage pipes of a high-security prison or the asylum where they are held without charge, or else circulated, samizdat-style, among sympathizers. The authors of these narratives are themselves the subjects of others. So the characters created by Volodine become the authors of his work, such that Antoine Volodine is just one name among the many contributors to the literature of the post-exotic world. With formal roots in science fiction and thematic sources in France's continuing nostalgia for the revolutionary road, Volodine's dreamworld seems quite unrelated to the main trends of contemporary writing, yet it forms one of the most ambitious literary projects of our times. Couched in language of exquisite precision and grace, Volodine's not entirely imaginary construction of a ruined world simultaneously denies individual authorship and reasserts human individuality through the memorializing function of storytelling.
Keywords: Volodine; French Revolution; Revolution; storytelling; narratives; French nostalgia; nostalgia; revolutionary road